Trade flows in renewable energy industry in malaysia: Evidence from a gravity model - Khudari M. (Mattingley Publishing, 2023)
Environmental regulations; Environmental technology; International trade; Manufacture; Renewable energy resources; CO2 emissions; Domestic manufacturing; Gravity model; Renewable energies; Renewable Energy industries; Solar pv industries; Technological development; Use of renewable energies; Competition